Isi Kandungan Surat al-Mulk dan al-Waqi’ah dan Korelasinya dengan Konsep Keberkahan Hidup - Adung Abdur Rohman (UIN Sunan Gunung Djati Bandung, 2021)
Living Quran in terminology means the Qur'an that lives on par with the term Qur'an in everyday life, namely the Qur'an that lives amid everyday life. The primary objectives of this research are 1) Knowing the essence of the content of Surat al-Mulk and Al-Waqi'ah, 2) Studying the correlation of Surat Al-Mulk and Surat Al-Waqi'ah with the concept of life, 3) Knowing the responses of the Jambu Islamic Boarding School students al Islamy against the habit of reading Surat Al-Mulk and Al-Waqi'ah. This study uses a qualitative approach. Data collection was carried out using interview, observation, and documentation instruments. The results of this study are as follows: First, the main points of Surah Al-Mulk consist of life, death, trials for humans, God's power in creating a multi-layered sky, God's command to pay attention to the universe, the threat of doom for people. Kafir, God's promise to the believers, God's warning to people who disobey Him. The contents of the letter Al-Waqiah tell about how the story happened. There is compensation for the believer and the disbeliever. As for fadhilah from Surah Al-Waqiah, among others, abundant sustenance, protection from harm, ease of death, and death will not fall into poverty. Second, based on interviews, the Kebon Jambu al-Islamy Islamic Boarding School students responded very well to the habit of reading Al-Mulk's letter like the dluha prayer and reading Al-Waqiah's letter like the evening prayer. As a result, the Kebon Jambu Islamic Boarding School seemed to get a blessing from reading the letter, as evidenced by the number of students and the increase in physical buildings in the pesantren environment. All of this is believed to be due to the blessing of reading Surah Al-Mulk and Surah Al-Waqiah. Finally, this study proved a correlation between reading Surah Al-Mulk and Al-Waqiah with the benefits of life.